Role of plaque inflammation in symptomatic carotid stenosis - Zheng, Yilong; Lim, Mervyn Jun Rui; Tan, Benjamin Yong-Qiang; Chan, Bernard Poon Lap; Paliwal, Prakash; Jonathan, Ong Jia Yuan; Bharatendu, Chandra; Chan, Amanda Chee Yun; Yeo, Leonard Leong Litt; Vijayan, Joy; Hong, Chiew S.; Chee, Young Heng; et al. (Frontiers in Neurology, 2023)
Objective: Prior studies have shown that plaque inflammation on FDG-PET and the symptomatic carotid atheroma inflammation lumen-stenosis (SCAIL) score were associated with recurrent ischemic events, but the findings have thus far not been widely validated. Therefore, we aimed to validate the findings of prior studies. Methods: A single-center prospective cohort study that recruited patients with (1) recent TIA or ischemic stroke within the past 30 days, (2) ipsilateral carotid artery stenosis of ≥50%, and (3) were not considered for early carotid revascularization. The (1) maximum standardized uptake value (SUVmax) of the symptomatic carotid plaque, (2) the SCAIL score, and (3) stenosis severity of the symptomatic carotid artery were measured for all patients. The outcomes were (1) a 90-day ipsilateral ischemic stroke and (2) a 90-day ipsilateral symptomatic TIA or major adverse cardiovascular event (MACE). Results: Among the 131 patients included in the study, the commonest cardiovascular risk factor was hypertension (95 patients, 72.5%), followed by diabetes mellitus (77 patients, 58.8%) and being a current smoker (64 patients, 48.9%). The median [IQR] duration between the index cerebral ischemic event and recruitment to the study was 1 [0, 2.5] days. The median [IQR] duration between the index cerebral ischemic event and FDG-PET was 5 [4, 7] days. A total of 14 (10.7%) patients had a 90-day stroke, and 41 (31.3%) patients had a 90-day TIA or MACE. On comparison of the predictive performances of the SCAIL score and SUVmax, SUVmax was found to be superior to the SCAIL score for predicting both 90-day ipsilateral ischemic stroke (AUC: SCAIL=0.79, SUVmax=0.92) (p<0.001; 95% CI=0.072, 0.229) and 90-day TIA or MACE (AUC: SCAIL=0.76, SUVmax=0.84) (p=0.009; 95% CI=0.020, 0.143). Conclusion: Plaque inflammation as quantified on FDG-PET may serve as a reliable biomarker for risk stratification among patients with ECAD and recent TIA or ischemic stroke. Future studies should evaluate whether patients with significant plaque inflammation as quantified on FDG-PET benefit from carotid revascularization and/or anti-inflammatory therapy.